Risk Identification of Private Entities in Public-Private Partnership (PPP) Projects for Water Supply Systems (SPAM) - Fakhrudin Naufal Ansori; Farida Rachmawati (LPPM Institut Pendidikan Nusantara Global, 2026)
The development of Water Supply System (SPAM) infrastructure through the Public-Private Partnership (PPP) scheme serves as a strategic solution to the state's fiscal limitations. However, its implementation faces challenges of high-risk complexity, particularly regarding the resilience of private partners post-construction. Failure to anticipate risks from the bidding stage often leads to financial distress or service failure during the concession period. This study aims to identify and map the dominant risk profile inherent to private entities during the partner selection phase of SPAM PPP projects. Using a descriptive quantitative method, data were collected through structured questionnaires from 7 expert respondents representing key stakeholders, selected via purposive and snowball sampling techniques. Data analysis was performed by calculating the Severity Index to map risks into a probability and impact matrix. The results reveal a significant risk distribution pattern, where the majority of risks are concentrated in the red zone (high/extreme risk) and orange zone, with none in the safe zone. Specifically, the study identified three highest-risk variables: